Protein synthesis increases with photosynthesis via the stimulation of translation initiation. (February 2020) - Tcherkez, Guillaume; Carroll, Adam; Abadie, Cyril; Mainguet, Samuel; Davanture, Marlène; Zivy, Michel
Highlights: Carbon allocation to proteins is about 1–2.5 % of net photosynthesis and is unrelated to total amino acid provision. Photosynthesis correlates to polysome abundance and phosphorylation of ribosomal proteins and translation initiation factors. Protein synthesis activity and translation correlate positively with photosynthesis. Abstract: Leaf protein synthesis is an essential process at the heart of plant nitrogen (N) homeostasis and turnover that preferentially takes place in the light, that is, when N and CO2 fixation occur. The carbon allocation to protein synthesis in illuminated leaves generally accounts for ca . 1 % of net photosynthesis. It is likely that protein synthesis activity varies with photosynthetic conditions (CO2 /O2 atmosphere composition) since changes in photorespiration and carbon provision should in principle impact on amino acid supply as well as metabolic regulation via leaf sugar content. However, possible changes in protein synthesis and translation activity when gaseous conditions vary are virtually unknown. Here, we address this question using metabolomics, isotopic techniques, phosphoproteomics and polysome quantitation, under different photosynthetic conditions that were varied with atmospheric CO2 and O2 mole fraction, using illuminated Arabidopsis rosettes under controlled gas exchange conditions. We show that carbon allocation to proteins is within 1–2.5 % of net photosynthesis, increases with photosynthesis rate and is unrelated to total amino acid content. In addition, photosynthesis correlates to polysome abundance and phosphorylation of ribosomal proteins and translation initiation factors. Our results demonstrate that translation activity follows photosynthetic activity, showing the considerable impact of metabolism (carboxylation–oxygenation balance) on protein synthesis.